(untitled) (Linguostylistic Studies, 2023)
The policy of masking the ugly reality and creating a mythical attractive world by replacing words that denote certain concepts is not new. It is a widespread practice of totalitarian regimes. The British writer George Orwell first used the device of newspeak in the novel “1984”. The invasion of the Russian Federation on the territory of Ukraine has once again updated Newspeak and it became an active means of Kremlin propaganda. With the help of invented words, Russia tries to blur reality and to hide the truth (eg, “спецоперация” instead of “war”, “хлопОк” instead of “explosion”, “перегруппирование” instead of “retreat”, “жест доброй воли”, not “loss of control over previously conquered territory”). The study of effective language counteraction to hostile rhetoric seems to be particularly relevant. As the analysis of the Ukrainian-language segment of the Internet discourse shows, the reaction of Ukrainians to the obvious Kremlin lies and distortion of facts, protection from the aggressor at the verbal level is mainly laughter and irony. The objective of the article is to characterize the peculiarities of using the means of invective irony to counter hostile anti-Ukrainian propaganda. The public activist Serhii Sternenko’s blog in the information and news Internet resource Gazeta.ua (gazeta.ua/bloguser/129852) on the website of the publication (gazeta.ua/) was chosen as a case study. There, the author publishes news about Russian-Ukrainian war and positions his attitude towards them. The research was carried out on the material of the texts for the period from May 20, 2022 to May 2, 2023. Irony is not just a stylistic technique, but a complex linguistic and mental phenomenon that conveys the worldview of the author and expresses his critical attitude towards an object of ridicule. Ironic speech is a kind of resistance, as an informational opposition to Russian aggression cannot be emotionally neutral since it is a communication style characterized by a high degree of negative emotionality. In modern military discourse, irony is used as a method of linguistic aggression (mostly indirect), which primarily performs an invective function. Invectives are linguistic units that are used to insult an opponent. The study proves that in the conditions of active functioning of the Newspeak (a means of aggressive Russian propaganda), the language of Ukrainians has turned into a means of aggressive defense. Irony as an invective means of hidden linguistic aggression against Russia in Serhii Sternenko’s blog is expressed through allusion, metaphor, hyperbole, antithesis, paraphrase, phraseological units and precedent phenomena.